Effect of short-term inhalation of warm saline atomised gas on patients with non-cystic fibrosis bronchiectasis. Issue 1 (10th February 2020) - Zhong, Lihong; Xiong, Ying; Zheng, Zeguang; Liu, Ni; Hu, Jieying; Yang, Feng; Chen, Rongchang
Objective: Secretion clearance is advocated in non-cystic fibrosis bronchiectasis, but is often neglected in clinical treatment. The present study aimed to investigate the effect of inhaled 0.9% normal saline by ultrasonic nebuliser with warming (UNW) in stable non-cystic fibrosis bronchiectasis patients with purulent sputum. Methods: 27 stable patients were enrolled in a randomised crossover trial comprising 3 months of daily UNW aerosol therapy compared with 3 months of daily oral expectorant treatment. The outcomes were quality of life (assessed via the Leicester cough questionnaire (LCQ)), sputum characteristics, pulmonary function, 6-min walk distance (6MWD) and acute exacerbation frequency. Results: Compared with baseline, the sputum viscosity, sputum colour, LCQ score and 6MWD were significantly improved with UNW (p<0.05), and the improvements in sputum colour, LCQ score, 6MWD and inspirational capacity with UNW were significantly better than those achieved via treatment with oral expectorant (p<0.05). There were no significant differences between treatments in pulmonary function, sputum cytology classification and inflammatory factors of sputum. Conclusion: UNW aerosol therapy in non-cystic fibrosis bronchiectasis has small yet significant benefits. However, UNW does not improve the degree of inflammation. Curative effect of ultrasonic nebulisation with warming for stable non-cystic fibrosis bronchiectasis patients with sputum: a randomised crossover study http://bit.ly/2RjyfET